Photocatalytic degradation of aromatic pollutants in aqueous solution over TiO2catalyst - Chonlada Theerakarunwong (2018)
© 2015, Chiang Mai University. All rights reserved. The photocatalytic degradation of two organic aromatic compounds; benzene and toluene, as environmental decontamination by using TiO 2 photocatalyst under UV irradiation was studied. It was noted that anatase TiO 2 nanoparticles had crystalline structure and spherical particles morphology. The average size was about 20 nm with the specific surface area of 83 m 2 /g. The photocatalytic performance of these TiO 2 catalysts was found that the percent removal depended on the dose of TiO 2 and H 2 O 2 . The 3 wt% TiO 2 displayed highest photominerizer since TiO 2 particles generating electron-hole pairs both at the surface and within the TiO 2 semiconductor itself and interacted with the organic molecules. The degradation of benzene and toluene increased along with increasing H 2 O 2 due to the precence of H 2 O 2 promotes the hydroxyl radicals. The photocatalyst removed 80% benzene and toluene within 60 min after UV irradiation more than the commercial P25 powder. In addition, the photocatalytic degradation of those compounds followed the pseudo-first-order kinetic.